Polymorphisms in Cytokine Receptor and Regulator Genes are Associated with Levels of Exercise in Women Prior to Breast Cancer Surgery. Issue 1 (January 2023) - Haas, Nadia D.; Viele, Carol; Paul, Steve M.; Abrams, Gary; Smoot, Betty; Melisko, Michelle; Levine, Jon D.; Miaskowski, Christine; Kober, Kord M.
Background: Little is known about the genetic characteristics associated with exercise in women undergoing breast cancer surgery.Purpose: In a sample of women who were evaluated prior to breast cancer surgery ( n = 310), we evaluated for differences in demographic and clinical characteristics between patients who did and did not exercise on a regular basis and evaluated for associations between polymorphisms in genes for pro- and anti-inflammatory cytokines, their receptors, and their transcriptional regulators.Methods: Patients completed an investigator-developed exercise questionnaire. Based on the recommended level of exercise (≥150 minutes/week), survivors were classified into no exercise (NoEx), less exercise (LessEx), or recommended exercise (RecEx) groups. Candidate gene analyses were done to identify relationships between polymorphisms and exercise group membership (i.e., NoEx vs. RecEx). Only 23.5% of the total sample met the recommendations for regular exercise.Results: Compared to the RecEx group ( n = 78), patients in the NoEx group ( n = 120) had less education; were less likely to report being White or Asia/Pacific Islander; more likely to report a lower household income; had a higher body mass index (BMI), had a poorer functional status; had a higher comorbidity burden; were more likely to self-report high blood pressure; and were more likely to have received neoadjuvant chemotherapy. Polymorphisms in IFNGR1 and NFKB1 were associated with membership in the NoEx group.Conclusions: While they warrant replication, our findings suggest that variations in cytokine-related genes may play a role in exercise behavior, and that clinicians need to assess for barriers to regular exercise and educate patients on its benefits.